A model of coupled thermosolutal convection and thermoelasticity in soft rocks with consideration of water vapor absorption. (June 2016) - Chen, Y.Q.; Yu, H.Z.; Zhu, Q.Y.
Highlights: Double-diffusive convection coupled with thermoelasticity and water absorption is studied. Increasing of Rayleigh, Darcy numbers and buoyancy ratio intensifies the convective flow. Water absorption effects have significant influence on the strength and deformation of soft rocks. Redistribution of porosity and volume strain are in correspondence with the isotherm. Abstract: The unsteady double-diffusive natural convection flow in a rectangular enclosure filled with soft rocks which are subjected to humid air, including water vapor absorption and thermoelasticity, is studied numerically. The high order compact finite difference schemes are adopted for better simulation of this problem, and a Darcy–Brinkman–Forchheimer extended model combined with the absorption and thermoelasticity effects is introduced. The effects of the thermal and solutal Rayleigh numbers, hygroscopicity, Darcy numbers and thermoelasticity on the flow are investigated in detail. Results are presented in the form of streamlines and isolines of temperature and mass fraction as well as the plots of average Nusselt and Sherwood numbers over the walls under different conditions. The flow structure develops from conduction-dominated to steady convection-dominated as increasing Rayleigh number or increasing buoyancy ratio as well as increasing Darcy numbers. The thermoelasticity effects of soft rocks play an important role in the analysis of thermal convection flow by the change of temperature and permeability, while the water vapor absorption effects may have a slight effect on the flow in the beginning and vanish with the absorption effects becoming weak. Nevertheless, the effect may significant reduce the mechanical strength properties of soft rocks.